ANALISIS PERAN GURU DALAM PEMBENTUKAN KARAKTER SISWA DI SD NEGERI 01 SEBETUNG MENYALA - Karni; Hendrikus Torimtubun (STKIP Subang, 2026)
This research is motivated by the continued discovery of student character problems, such as a lack of honesty, discipline, and responsibility in learning activities at SD Negeri 01 Sebetung Menyala. Teachers have a very important role in shaping students' character through role models, habituation, guidance, and supervision during the learning process. This study aims to determine the role of teachers in shaping students' character in the aspects of honesty, discipline, and responsibility at SD Negeri 01 Sebetung Menyala. This study uses a descriptive method with a qualitative approach. The research subjects consisted of teachers of grades II, IV, and V as well as students of grades IV and V. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that teachers have carried out their roles well in shaping students' character. In the aspect of honesty, teachers instill the value of honesty through role models, the habit of not cheating, and providing advice to students. In the aspect of discipline, teachers apply class rules consistently, provide examples of arriving on time, and get students used to obeying school rules. In terms of responsibility, teachers guide students to complete assignments independently and provide support throughout the learning process. Supporting factors for student character development include collaboration between teachers and parents, a conducive school environment, and the implementation of good school rules and habits. Inhibiting factors include differences in students' family backgrounds, the influence of their social environment, and the uncontrolled use of technology and social media. Based on the research findings, it can be concluded that teachers play a crucial role in shaping students' character through role models, habits, mentoring, and consistent application of discipline. Therefore, ongoing collaboration between schools, teachers, and parents is necessary to optimize student character development.